Some solution to develop the card payment activity in Viet Nam Joint Stock Comercial Bank for Industry and Trade_VietinBank for the period of 2012_2017 - Chử, Thanh Tâm (Đại học Quốc gia Hà Nội, 2016)
Vietnam Joint Stock Commercial Bank for Industry and Trade is one of the four largest banks in Viet Nam. VietinBank has emerged as the most effective and profitable bank in Vietnam banking sector, with the goal of becoming the number one financial group in Vietnam and has positioned in Asia within 3 to 5 years, one of present strategies to achieve above objectives, VietinBank determined that developing retail banking services as important part constitutes strategy. In which, develop card account product, payment card, especially card payment service is considered the core product in the context of extremxe active card market in Vietnam today. To support VietinBank in building solutions, the thesis will analyze opportunities and challenges from the market, at the same time clarify and analyze the strengths and weaknesses from the VietinBank, from which to set out some measures to improve efficiency of VietinBank card payment business. These measures are feasible, close to the reality of VietinBank, if applied they will actually support VietinBank further improve competitiveness, promote strength, resolve weaknesses. From which completely shorten the gap with the leading banks and compellingly striving to leader in short time.